DIGITAL RHETORIC AND THE TRANSFORMATION OF POLITICAL COMMUNICATION: AN ANALYSIS OF ETHOS, PATHOS, AND LOGOS IN POST-TRUTH ERA SOCIAL MEDIA CAMPAIGNS - Jodi Al-pares (LinguAmerta, 2025)
This study examines the transformation of political rhetoric in the digital age, specifically analyzing how classical Aristotelian rhetorical elements (ethos, pathos, and logos) are adapted and manifested in social media political campaigns. Using a qualitative descriptive approach with content analysis methodology, this research analyzes political communication patterns on various social media platforms during the 2024 Indonesian regional elections. The findings reveal that digital political rhetoric demonstrates significant adaptations: ethos is constructed through algorithmic credibility and viral authenticity, pathos is amplified through emotional contagion mechanisms and micro-targeting, while logos is fragmented into bite-sized information packages optimized for platform-specific algorithms. The study concludes that digital political rhetoric creates new forms of persuasion that challenge traditional democratic discourse, requiring new frameworks for understanding political communication in the post-truth era.